2003
DOI: 10.1007/s00277-003-0711-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of weak D in Taiwanese

Abstract: Two genes, RHD and RHCE, encode the antigens of the RH blood group system. The weak D phenotype is caused by many different RHD alleles encoding aberrant RhD proteins, resulting in distinct serologic phenotypes and anti-D immunization. We analyzed seven weak D phenotypes excluding D(el), using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and direct sequencing methods to detect the changes of all ten RHD exons. The results show that there are four types of weak D in Taiwanese: o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
2
20
1
1
Order By: Relevance
“…The improved resolution in RHD genotyping strategy has allowed a diverse array of RHD variants beyond RHD*weak D type 1, RHD*weak D type 2 and RHD*weak D type 3 to be defined. This included East Asianassociated RHD variants such as RHD*weak partial 15 and RHD*weak D type 33, and African-associated variants such as RHD*weak partial 4Á0, RHD*weak partial 4Á1 and RHD*weak D type 90 [7,[22][23][24][25][26][37][38][39]. It also included a novel RHD*c.939+3A>C variant that had exhibited a nucleotide substitution in Intron 6 and a weak partial D-epitope profile lacking epD1Á2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved resolution in RHD genotyping strategy has allowed a diverse array of RHD variants beyond RHD*weak D type 1, RHD*weak D type 2 and RHD*weak D type 3 to be defined. This included East Asianassociated RHD variants such as RHD*weak partial 15 and RHD*weak D type 33, and African-associated variants such as RHD*weak partial 4Á0, RHD*weak partial 4Á1 and RHD*weak D type 90 [7,[22][23][24][25][26][37][38][39]. It also included a novel RHD*c.939+3A>C variant that had exhibited a nucleotide substitution in Intron 6 and a weak partial D-epitope profile lacking epD1Á2.…”
Section: Discussionmentioning
confidence: 99%
“…Weak D types 4Á0 and 4Á1 have been reported as frequently occurring alleles in African populations from Egypt, Tunisia, Ethiopia and South Africa [7,21,22]. Weak D type 15 and 33 predominate in East Asian donor populations from Japan, China and Taiwan [23][24][25][26]. In 2000, a study of 99 Australian blood donors with a weak D phenotype showed the majority of RHD variants comprised weak D types 1, 2 or 3 (n = 88), similar to those reported in Europe and Canada [27].…”
Section: Introductionmentioning
confidence: 99%
“…To date, at least 27 weak D alleles and 14 partial D alleles have been identified in the Chinese population (Tables and ), which are low compared with the hundreds found in the Caucasian population. RHD*weak partial 15 and RHD*DVI.3 are the most common D variant alleles, accounting for more than 70% of D variants in the Chinese population.…”
Section: Rhd Genotypingmentioning
confidence: 92%
“…To date, at least 27 weak D alleles [43,46,47,[58][59][60][61][62][63]] and 14 partial D alleles [46,57,58,61] have been identified in the Chinese population (Tables 2 and 3), which are low compared with the hundreds found in the Caucasian Xi'an [46] (n = 72) Shenzhen [43] (n = 3)…”
Section: Variants Genotypingmentioning
confidence: 99%
“…It was in 1999, when Wagner et al [6] described the molecular basis of weak D phenotypes, hereby opening the way for the unambiguous definition and typing of every single 'D u ' sample. Shortly thereafter an impressive number of articles described the frequency of weak RHD alleles found in sample collections of phenotypically weak Ds analyzed in a variety of populations [7][8][9].…”
Section: Introductionmentioning
confidence: 99%